An analysis on the implementation of the Social Organizations in the schools of State of Goiás: The public resources in question - Souza, Fábio Araujo de; Flores, Maria Marta Lopes (Revista Eletrônica de Educação, 2017)
This study aims to analyze the implementation process of shared management between the State Secretary of Education, Culture and Sport, and a Social Organization (OS) in basic education State education network of Goiás, Brazil, emphasizing the issue of public funding in education. The research is qualitative-quantitative and the investigation has an exploratory nature. To conduct the research, it was carried out a survey in the State budget during 2016, on legislations of the deployment process of shared management. It was also performed a bibliographical survey on OSs and in the news websites and Government officials from entities focused on the theme, as well as in scientific articles and other sources relevant to the subject. The research has found that the OS may have a substantive profit with the shared management, in view of the voluminous resources provided to implement the project in the State of Goiás public education in the budget for 2016. In addition, the research points out that the Career Plan, hiring by public competition and the appreciation through the Wage Floor of National Professional Education professionals can stay committed due to the shared management in the State of Goiás. Keywords: Social organization. Public resources. Shared management. References ALMEIDA, Mônica Piccolo. Reformas neoliberais no Brasil: a privatização nos governos Fernando Collor e Fernando Henrique Cardoso. 2010. Tese (Doutorado em História) – Departamento de História, Instituto de Ciências Humanas e Filosofia, Universidade Federal Fluminense, Rio de Janeiro, 2010. BRASIL. Palácio do Planalto. Constituição Federal de 1988. Brasília [on-line]. Available on:<http://www.planalto.gov.br/ccivil_03/constituicao/ConstituicaoCompilado.htm>. Accessed on February 12th 2016. BRASIL. Palácio do Planalto. Lei n. 9.394 de 20 de dezembro de 1996. Estabelece as diretrizes e bases da educação nacional. Brasília [on-line].Available on: < http://www.planalto.gov.br/ccivil_03/leis/L9394.htm>. Accessed on February 12th 2016. BRASIL. Palácio do Planalto. Lei n. 11.494 de 20 de junho de 2007. Regulamenta o Fundo de Manutenção e Desenvolvimento da Educação Básica e de Valorização dos Profissionais da Educação – FUNDEB, Brasília [on-line]. Available on: <http://www.planalto.gov.br/ccivil_03/_ato2007-2010/2007/lei/l11494.htm>. Accessed on February 12th 2016. BRASIL. Ministério da Educação. Manual de orientação do Fundeb. Brasília [on-line]. Available on: < www.fnde.gov.br/arquivos/category/196-manuais?...manual...fundeb>. Accessed on February 12th 2016. BRASIL. Ministério da Educação. Sistema de Consulta à matrícula do Censo Escolar. Brasília [on-line]. Available on: < http://portal.inep.gov.br/basica-censo-escolar-matricula>. Accessed on February 12th 2016. BRASIL. Lei n. 9.637, de 15 de maio de 1998. Dispõe sobre a qualificação de entidades como organizações sociais, a criação do Programa Nacional de Publicização, a extinção dos órgãos e entidades que menciona e a absorção de suas atividades por organizações sociais, e dá outras providências. Available on: <http://www.planalto.gov.br/ccivil_03/leis/L9637.htm> Accessed on March 12th 2016. BRASIL. Supremo Tribunal Federal. Ação Direta de Inconstitucionalidade – ADIN 1.923/DF. Available on: <http://www.mpsp.mp.br/portal/page/portal/cao_cidadania/Terceiro_Setor/Jurisprudencia_ACP/Voto__ADI1923LF.pdf>. Accessed on March 7th. 2016. BRASIL. Ministério da Educação. Sistema FNDElegis. Available on: < https://www.fnde.gov.br/fndelegis/action/ActionDatalegis.php?acao=abrirTreeview&cod_menu=709&cod_modulo=11>. Accessed on March 7th 2016. BRESSER-PEREIRA, Luiz Carlos. A Reforma do Estado dos anos 90: lógica e mecanismos de controle. Brasília, DF: Ministério da Administração Federal e da Reforma do Estado, 1997. GOIÁS. Secretaria de Estado de Educação e Cultura e Esporte. Secretária esclarece sobre a destinação do Fundeb para escolas com OSs, 4 mar. 2016. Disponível em: http://portal.seduc.go.gov.br/SitePages/Noticia.aspx?idNoticia=1832, 2016a. Accessed on March 7th. 2016. GOIÁS. Secretaria de Estado de Educação e Cultura e Esporte. Aviso de Chamamento Público n. 001/2016. Disponível em: <http://www.seduc.go.gov.br/documentos/chamamentopublico2016/01/EDITAL%20DE%20CHAMAMENTO%20P%C3%9ABLICO%20MACRORREGI%C3%83O%20VI%20-%20AN%C3%81POLIS.pdf>, 2016b. Accessed on March 7th 2016. GOIÁS. Secretaria de Estado de Gestão e Planejamento. LOA - Lei n. 19.225, de 13/01/2016, orça a receita e fixa e despesa do Estado para o exercício de 2016. Disponível em: <http://www.sgc.goias.gov.br/upload/arquivos/2016-01/orcamento-geral-estado-goias-2016-v1.pdf >, 2016c. Accessed on March 7th 2016. MEIRA, Júlio Cesar. As organizações sociais e as parcerias na administração. Revista Ágora, Vitória, n.15, p. 90-109, 2012. MINISTÉRIO PÚBLICO DO ESTADO DE GOIÁS et al. Inquérito Civil. Available on:<http://www.mpgo.mp.br/portal/arquivos/2016/02/16/17_36_26_430_Recomenda%C3%A7%C3%A3o_MPE_MPF_e_MPC_suspens%C3%A3o_edital_OSs_nas_escolas.pdf>. Accessed on March 7th 2016. NOVA ESCOLA. Exclusivo: quem vai administrar as escolas de Goiás? Available on: <http://revistaescola.abril.com.br/politicas-publicas/radiografia-oss-goias-938045.shtml>. Accessed on March 7th 2016. PINTO, Elida Graziane. Organizações sociais e reforma do Estado no Brasil: riscos e desafios nesta forma de institucionalizar a parceria Estado-Sociedade organizada. Concurso de Ensayos del Clad Administración Pública y Ciudadanía, v. 14, p. 47-81, 2000. SOUZA, Raquel; SILVA, Marcelo. Reestruturações na administração pública brasileira e os desdobramentos na educação superior. Linhas Críticas, v. 14, n. 27, p. 263-282, 2008. TVUFG. Entrevista com a secretária de Educação, Cultura e Esporte do estado de Goiás, Raquel Figueiredo Alessandri Teixeira. Boletim Conexões, 7 jan. 2016. Available on <https://www.youtube.com/watch?v=iHbA-mG5Fp0>. Accessed on March 7th 2016.